Selecting Optimal Pedestrian Crossing Using Multi-criteria Decision-making - Šimunović, Ljupko; Grgurević, Ivan; Pašagić Škrinjar, Jasmina (Promet - Traffic&Transportation, 2012)
Pedestrian crossings are the critical points in the traffic network that need to enable pedestrians to safely cross the road. The safety level depends on the type of pedestrian crossing. The differences between individual types of pedestrian crossings can be noted also in relation to other criteria such as the price, energy, environmental impact, accessibility, etc. Besides, various groups of users assess the quality service differently, even when this refers to the same type of pedestrian crossing. Therefore, optimal solution of a pedestrian crossing has to be selected based on a comprehensive and rational analysis and application of adequate software tools. The selection methodology of an optimal pedestrian crossing is defined using a multi-criteria analysis. In order to view the problem as a whole, four scenarios of evaluating alternatives are foreseen. Four different groups of stakeholders: traffic experts, investors, groups of persons with disabilities and healthy persons (persons not included in the previous three stakeholder groups), who use a pedestrian crossing (according to different age, disability, perception of personal safety, etc.), assessed the importance of the offered criteria. Different groups of users have different preferences in relation to individual groups of criteria, depending on their interests and needs. One group finds the criterion of pedestrian safety the most important one, others think that finances are most important (the cost of construction), some think that accessibility is the most important issue, etc. The solutions obtained in this manner provide insight into the advantages and drawbacks of individual versions. This makes it easier for the decision-makers to select only one variant / alternative from a group of the offered solutions in compliance with the defined criteria and sub-criteria with the aim of defining an optimal pedestrian crossing for a certain spatial and traffic location. KEY WORDS: pedestrian crossing, multi-criteria decision-making, analytical hierarchy process